Nanomaterial-Based Drug Delivery System Targeting Lymph Nodes - Zesheng Cheng; Haiying Que; Li Chen; Qiu Sun; Xiawei Wei (MDPI AG, 2022)
The lymphatic system plays an indispensable role in humoral balance, lipid metabolism, and immune regulation. The lymph nodes (LNs) are known as the primary sites of tumor metastasis and the metastatic LNs largely affected the prognosis of the patiens. A well-designed lymphatic-targeted system favors disease treatment as well as vaccination efficacy. In recent years, development of nanotechnologies and emerging biomaterials have gained increasing attention in developing lymph-node-targeted drug-delivery systems. By mimicking the endogenous macromolecules or lipid conjugates, lymph-node-targeted nanocarries hold potential for disease diagnosis and tumor therapy. This review gives an introduction to the physiological functions of LNs and the roles of LNs in diseases, followed by a review of typical lymph-node-targeted nanomaterial-based drug-delivery systems (e.g., liposomes, micelles, inorganic nanomaterials, hydrogel, and nanocapsules). Future perspectives and conclusions concerned with lymph-node-targeted drug-delivery systems are also provided.